Affecting Factors of Interest in Using Peer-to-Peer Lending Services: Financial Behavior as a Mediator - Mardiyani; Ahmad Maulana; Rita Avia Triana (PT FORMOSA CENDEKIA GLOBAL, 2025)
In order to ascertain how risk perception and financial literacy affect students' interest in using P2P lending services, this study employs financial behavior as a mediating variable. This study is causally related to the FEB UGJ student population, with a sample of 384 students based on the Likert scale. The data was analyzed using the Structural Equation Modeling (SEM) method. The results show that financial behavior, influenced by risk perception and financial literacy, mediates students' interest in peer-to-peer lending. This study emphasizes the importance of teaching students financial literacy and risk awareness to encourage responsible fintech use. To encourage responsible P2P lending use, regulators and educational institutions need to increase students' knowledge of risk.